Sesame Street. [videorecording (DVD)] Being brave - Gandolfini, James (Sesame Workshop, 2013)
Uh-oh! There's a monster at the end of this DVD! Help children learn to overcome their fears with Sesame Street's special brand of honesty and humor. Elmo, Grover, and friends learn strategies to deal with scary thunderstorms, strange shadows, unfamiliar dogs, and buzzing bees. Filled with great ideas for managing common preschool fears. Includes a special appearance by James Gandolfini.